The effects of carbohydrate, unsaturated fat, and protein intake on measures of insulin sensitivity: results from the OmniHeart trial - Gadgil, Meghana D; Appel, Lawrence J; Yeung, Edwina; Anderson, Cheryl A M; Sacks, Frank M; Miller, 3rd, Edgar R (Diabetes care, 2013)
Impaired insulin sensitivity increases the risk of cardiovascular disease. Although calorie restriction and weight loss increase insulin sensitivity, the effects of modifying macronutrient composition on insulin sensitivity are uncertain. The purpose of this study is to determine the effects on insulin sensitivity of a carbohydrate-rich diet (CARB; similar to the Dietary Approaches to Stop Hypertension [DASH] diet), a protein-rich diet (PROT; protein predominantly from plant sources), and an unsaturated fat-rich diet (UNSAT; predominantly monounsaturated). This study was a randomized, controlled, three-period, crossover feeding study. The study participants were 164 individuals with prehypertension or stage 1 hypertension without diabetes. Diets were administered for 6 weeks each, with a washout period between diets of 2-4 weeks. Weight was held constant throughout the study. For our primary outcome, we calculated the quantitative insulin sensitivity check index (QUICKI) using the end-of-period fasting serum glucose and insulin. QUICKI is a validated measure of insulin sensitivity. The primary analyses used generalized estimating equations. At baseline, mean (SD) BMI was 30.2 (6.1) kg/m(2), and mean (SD) QUICKI was 0.35 (0.04). The UNSAT diet increased QUICKI by 0.005, more than the CARB diet (P = 0.04). PROT had no significant effect compared with CARB. A diet that partially replaces carbohydrate with unsaturated fat may improve insulin sensitivity in a population at risk for cardiovascular disease. Given the well-recognized challenges of sustaining weight loss, our results suggest an alternative approach for improving insulin sensitivity.